Theory, practice and research in nursing: Marie-Luise Friedmann in conversation with Rafael Pineda Perdomo - Pineda Perdomo, Rafael (Investigación y Educación en Enfermería, 2010)
Transcription of the interview that Doctor Marie-Luise Friedmann gave to Nelly Garzon Alarcon and the author during her visit to Colombia in the year of 2009 in which the importance of re-searchers’ training for the development of nursing as science and occupation was discussed.